Investigating the Acquisition of Affixes by a Four-Year-Old Girl - M. Shabir (ENGLISH, 2015)
This paper tries to investigate the acquisition of Indonesian language affixes by a four-year-old girl. Using an exploratory design, this research, which spent two months period of observation, reveals that object of the study has not only acquired the simple affixes (combination of prefix and suffix) but also started showing her potency of producing the complex ones (the combination of prefix, infix, and suffix). However, the production of such complex affixes (the combination of prefix, infix, and suffix) can not be automatically categorized as the acquired ones due to their rare occurrences. It is suggested that the next similar research to be applied to other four years old girls for generalization purpose.